Host–guest materials with room temperature phosphorescence: Tunable emission color and thermal printing patterns. (17th October 2020) - Wang, Yunsheng; Yang, Jie; Gong, Yanxiang; Fang, Manman; Li, Zhen; Tang, Ben Zhong
Abstract: The research of purely organic materials with long afterglow has drawn more and more attention, especially for those with stimulus‐response characteristic. So far, this kind of material is really very scarce and their performance is not good enough. In this study, we successfully developed an efficient heating‐responsive room‐temperature phosphorescence material with phosphorescence efficiency and lifetime up to 13.4% and 2.08 s through the simple host–guest doping strategy. Further on, by introducing the additional energy acceptor of fluorescein with concentration‐dependent emission to construct ternary doping systems, the afterglow color was extended from blue to yellow. Accordingly, the multicolor thermal printings have been easily realized, showing the great practical application prospects. Abstract : In this study, a color‐tunable organic afterglow system with thermal response characteristic was developed by introducing the additional energy acceptor of fluorescein with concentration‐dependent emission. Accordingly, the multicolor thermal printings have been easily realized, showing the great practical application prospects.